Perceptions toward a pilot project on blended learning in Malaysian family medicine postgraduate training: a qualitative study - Salim, Hani; Ping, Yein Lee; Shariff Ghazali, Sazlina; Siew, Mooi Ching; Ali, Hanifatiyah; Shamsuddin, Nurainul Hana; Mawardi, Maliza; Kassim, Puteri Shanaz Jahn; Awang Dzulkarnain, Dayangku Hayaty (BioMed Central, 2018)
Background:Blended learning (BL) is a learning innovation that applies the concept of face-to-face learning and online learning. However, examples of these innovations are still limited in the teaching of postgraduate education within the field of family medicine. Malaysian postgraduate clinical training, is an in-service training experience and face-to-face teaching with the faculty members can be challenging. Given this, we took the opportunity to apply BL in their training. This study provides an exploration of the perceptions of the educators and students toward the implementation of BL.Methods:A qualitative approach was employed using focus group discussions (FGD) and in-depth interviews (IDI)at an academic centre that trains family physicians. Twelve trainees, all of whom were in their hospital specialty’srotations and five faculty members were purposively selected. Three FGDs among the trainees, one FGD and two IDIs among the faculty members were conducted using a semi-structured topic guide. Data were collected through audio-recorded interviews, transcribed verbatim and checked for accuracy. A thematic approach was used to analyse the data.Results:There were four main themes that emerged from the analysis. Both educators and trainees bill the perspective that BL encouraged continuity in learning. They agreed that BL bridges the gap in student-teacher interactions. Although educators perceived that BL is in concordance with trainees learning style, trainees felt differently about this. Some educators and trainees perceived BL to be an extra burden in teaching and learning.Conclusion:This study highlights a mix positive and negative perceptions of BL by educators and trainees. BL were perceived positively for continuity in learning and student-teacher interaction. However, educator and learner have mismatched perception of learning style. BL was also perceived to cause extra burden to both educators and learners. Integrating BL to a traditional learning curriculum is still a challenge. By knowing the strengths of BL in this setting, family medicine trainees in Malaysia can use it to enhance their current learning experience. Future studycan investigate different pedagogical designs that suit family medicine trainees and educators in promoting independent learning in postgraduate training.